Road premix management System - Tan, Cheng Chuan (2014)
This project deals with premix for road construction data from Seri Barat Mixed Sdn Bhd and its respective branches, Kuari Dinar Sdn Bhd, Damai Kuari Sdn Bhd, and Dimensi Timal Sdn Bhd in the state of Kelantan. The project is entitled as Road Premix Management System (RPMS). The objective of this project is to develop a Web-based managaement system for the companies in managing premix operations from different branches. There only administrator for main branch and branches that are defined as the main user in the system and there are no customer interactions with the system. The system is only integrated with sales and production and no others department even actually consists of three parts in the system. The system will determine the differences between the sales and production of premix according to the date. All the data entered will be saved in the database management system, called MySQL and Laravel framework is used for implementing the system.